2021
DOI: 10.3389/fmed.2021.652505
|View full text |Cite
|
Sign up to set email alerts
|

Dienogest as a Maintenance Treatment for Endometriosis Following Surgery: A Systematic Review and Meta-Analysis

Abstract: This study aimed to comprehensively assess the value of Dienogest (DNG) as a maintenance treatment following conservative surgery for endometriosis in terms of the outcomes of disease and pregnancy. We searched for relevant studies and trials up to November 2020 from PubMed, Cochrane Library, Medline, and EMBASE databases as well as the Web of Science. Patients who received DNG maintenance treatment were compared to those who received other treatments (OT), including the levonorgestrel-releasing intrauterine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…A growing body of research has demonstrated the unique advantages of DNG in the treatment of endometriosis: Patients treated with DNG after conservative surgery for endometriosis had a significantly lower risk of postoperative disease recurrence than those with expecting treatment ( 12 ); long-term use of DNG for rectosigmoid endometriosis can relieve symptoms ( 13 ); a significant increase in improvement in endometriosis lesions, pain symptoms, and quality of life were found in women taking DNG compared to women on continuous combined oral contraceptives ( 14 ); it is also an effective drug for controlling the pain symptoms associated with deep infiltrating endometriosis (DIE), even without reducing the volume of DIE nodules ( 15 ); it can be used for a long time and is well tolerated ( 16 ). DNG has therefore been recommended as an alternative method of controlling symptoms associated with endometriosis ( 17 ) and as maintenance therapy for patients with endometriosis to reduce the rate of disease recurrence after conservative surgery ( 18 ). However, the most common side effects of using DNG include irregular vaginal bleeding, weight gain, and headaches ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has demonstrated the unique advantages of DNG in the treatment of endometriosis: Patients treated with DNG after conservative surgery for endometriosis had a significantly lower risk of postoperative disease recurrence than those with expecting treatment ( 12 ); long-term use of DNG for rectosigmoid endometriosis can relieve symptoms ( 13 ); a significant increase in improvement in endometriosis lesions, pain symptoms, and quality of life were found in women taking DNG compared to women on continuous combined oral contraceptives ( 14 ); it is also an effective drug for controlling the pain symptoms associated with deep infiltrating endometriosis (DIE), even without reducing the volume of DIE nodules ( 15 ); it can be used for a long time and is well tolerated ( 16 ). DNG has therefore been recommended as an alternative method of controlling symptoms associated with endometriosis ( 17 ) and as maintenance therapy for patients with endometriosis to reduce the rate of disease recurrence after conservative surgery ( 18 ). However, the most common side effects of using DNG include irregular vaginal bleeding, weight gain, and headaches ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, our results demonstrate that a first-line drug for endometriosis, dienogest ( Andres Mde et al, 2015 ; Mori et al, 2015 ; Liu et al, 2021 ), is more efficient than the suppressive effect of PV in inhibiting the incidence of endometriosis. However, with regard to side effects, several clinical studies have reported that dienogest causes abnormal vaginal bleeding, weight gain, headaches, depressed mood, and dizziness ( Cosson et al, 2002 ; Uludag et al, 2021 ).…”
Section: Discussionmentioning
confidence: 76%
“…PV extract was administered orally at doses of 0.820 mg/kg and 4.100 mg/kg body weight or with 1 mg/ml of dienogest five times a week for 3 weeks after intraperitoneal inoculation of donor uterus tissue ( Figure 1A ). Dienogest, the first-line drug for endometriosis ( Andres Mde et al, 2015 ; Liu et al, 2021 ), was used as a control to evaluate the efficiency of PV in endometriosis. The PV group showed a significant reduction in cyst-like ectopic lesion volume compared to the untreated mice group.…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative medical treatment and pregnancy are protective factors associated with a lower recurrence rate of ovarian endometriosis after laparoscopic ovarian cystectomy [30]. Postoperative hormone suppression has been proposed as a means of reducing the need for reintervention following endometriosis surgery [7 ▪▪ ,28,30].…”
Section: Postoperative Hormone Use For Recurrence Of Diseasementioning
confidence: 99%
“…Progestogens aim to cause downregulation of oestrogen receptors and inhibit cell proliferation, inflammation, neovascularization and neurogenesis in endometriosis [6]. Dienogest (DNG) is a selective progestin that only binds to progesterone receptors and is characterized by good tolerance, antiandrogen activity with moderate inhibition of the hypothalamic-pituitary-axis and oestrogen levels [7 ▪▪ ]. DNG maintains therapeutic levels of oestrogen in the treatment of endometriosis without causing perimenopausal symptoms, loss of bone mineral density or growth of endometriosis.…”
Section: Introductionmentioning
confidence: 99%